2016
DOI: 10.1080/03610926.2015.1132328
|View full text |Cite
|
Sign up to set email alerts
|

Test for the mean matrix in a Growth Curve model for high dimensions

Abstract: In this paper, we consider the problem of estimating and testing a general linear hypothesis in a general multivariate linear model, the so called Growth Curve model, when the p × N observation matrix is normally distributed with an unknown covariance matrix.The maximum likelihood estimator (MLE) for the mean is a weighted estimator with the inverse of the sample covariance matrix which is unstable for large p close to N and singular for p larger than N . We modify the MLE to an unweighted estimator and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Before starting the point for estimating parameters, let us defined two jointly sufficient statistics for estimating parameters in the GCM and their respective distribution as found in Srivastava and Singull (2014). Those statistics are the mean XC (CC ) −1 C and the sum of squares matrix…”
Section: Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before starting the point for estimating parameters, let us defined two jointly sufficient statistics for estimating parameters in the GCM and their respective distribution as found in Srivastava and Singull (2014). Those statistics are the mean XC (CC ) −1 C and the sum of squares matrix…”
Section: Estimatorsmentioning
confidence: 99%
“…It is particularly useful when we have short to moderate time series where one cannot apply standard time series approaches. (Hamid et al(2010), von Rosen andKollo (2005), Srivastava and Singull (2015), Srivastava and Singull (2014), Srivastava and Singull (2017)) have shown that the mean structure for GCM is bilinear, on the contrary, for the ordinary Multivariate Analysis of Variance (MANOVA) model where the mean structure is linear. Since the introduction of GCM by Potthoff and Roy (1964), the model has been extensively explored by several authors including von Rosen and Kollo (2005), Khatri (1966), Rao (1958), Rao (1961), Rao (1966), Rao (1984), von Rosen (2018, for examples.…”
mentioning
confidence: 99%